Prevention of pathological fracture in fibrous dysplasia of proximal femur in a 24-year-old female a rare presentation - a case report - Supe, Amit; Mhatre, Jayesh; Modi, Nihar (International Journal of Research in Orthopaedics, 2021)
Fibrous dysplasia (FD) was historically mentioned in the medical literature in 1938 by Dr. Lichtenstein and in 1942 by Dr. Lichtenstein and Jaffe. The term Jaffe-Lichtenstein syndrome is sometimes used synonymously with monostotic FD or to denote cases of polyostotic FD with café au lait spots, but no endocrine dysfunction. Our case is a 24-year-old female, housewife presented to our hospital with a complaints of right hip pain and backache with difficulty in walking of 6 months duration. She had dull aching pain which increased in intensity with the course of time, there was no radiation, but was aggravated by movements. She was managed with dynamic hip screw along with curettage of the lesion and bone graft, after 9 months of follow up, she had no pain over her hip and there was calcification over the previous lesion, our patient had a very favourable outcome.